The Effect of Investment Climate on Productivity of Food and Beverages Industries in Eswatini - Hlanze, M. P.; Dlamini, Daniel Vusi; Ajetomobi, J. O. (Archives of Business Research, 2020)
Food security and job creation are among the top priorities of the government of Eswatini. To address these priorities, the government have made substantial amount of investment to support the agricultural sector over the years. Regardless of these policy intervention, Eswatini is still an importer of food and unemployment remains substantial high. The study examined the influence of investment climate on productivity of food and beverages industries in Eswatini. Findings of this study will assist the government of Eswatini to design focused policy interventions in order to attract more local and foreign direct investment.A Cobb-Douglas production function for Eswatini of manufacturing industries was estimated using 2006 cross sectional data from the World Bank to produce a measure of TFP for each industry. In addition, an extended Cobb-Douglas production function was estimated with investment climate variables for selected manufacturing industries.The results showed that manufacturing industries in Eswatini are labour intensive and competition from informal sectors is the main obstacle faced by manufacturing industries in Eswatini. The findings of the study further reveals that an increase in corruption cause a decrease in productivity. The study recommends investment in institutional reforms especially to fight against corruption and efficacy in the provision of public goods and services. It further recommends a resilient support and regulation of the informal sector.